Resetting the Respiratory Rhythm with a Spinal Central Pattern Generator - Meza, Roberto (eNeuro, 2019)
There is evidence that a variety of central and afferent stimuli, including swallowing, can produce phase resetting in the respiratory rhythmicity. Also, there are reports about the intrinsic linkage between locomotion and respiration. However, little is known about the interaction between the central pattern generators (CPGs) for scratching and respiration. The present study aims to examine whether the activation of scratching CPG produces phase resetting of the respiratory rhythm. We employed decerebrate cats to apply brief tactile stimuli to the pinna during the inspiratory-expiratory transition. We observed that those stimuli to the pinna not eliciting fictive scratching did not reset the respiratory rhythm. However, when the pinna stimuli elicited fictive scratching, then the respiratory rhythm exhibited a significant phase resetting. We also found interneurons in the medulla oblongata exhibiting phase resetting related to scratching-CPG episodes. This second finding suggests that this type of resetting involves brainstem components of the respiratory CPG. These results shed new light on the resetting action from a spinal CPG on the respiratory rhythm.